Family farming food acquisition program (PAA) - milk modality: design, instruments and intersectoral institutional arrangement (Research, Society and Development, 2023)
This article aims to discuss the design, instruments and intersectoral institutional arrangement of the Family Farming Food Acquisition Program (PAA) - Milk Modality, created in 2003 and linked to the structuring actions of the Zero Hunger Program. The PAA-Leite is a government strategy whose objective, among others, is to promote family farming production and provide food assistance to populations at risk. The theoretical perspective adopted is articulated in the understanding of PAA-Leite as part of a social protection system that prioritizes and defends the right of all people to healthy food and food sovereignty. Documentary analyses of laws, decrees, resolutions, plans and other documents are used to present, situate and problematize issues the PAA-Leite in the field of public policies to combat hunger and affirm food and nutritional security. It concludes that, despite the contradictions and limits of its implementation by municipalities and states, the PAA-Leite has a bold, innovative and socially relevant institutional design, as well as the potential to ensure access to food with high nutritional value for people in situations of social vulnerability, create conditions of prosperity and economic autonomy for milk supplying families and expand opportunities to remain in the countryside, especially for youth.